2014
DOI: 10.1371/journal.pone.0098483
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin Analogue Beraprost Inhibits Cardiac Fibroblast Proliferation Depending on Prostacyclin Receptor Activation through a TGF β-Smad Signal Pathway

Abstract: Previous studies showed that prostacyclin inhibited fibrosis. However, both receptors of prostacyclin, prostacyclin receptor (IP) and peroxisome proliferator-activated receptor (PPAR), are abundant in cardiac fibroblasts. Here we investigated which receptor was vital in the anti-fibrosis effect of prostacyclin. In addition, the possible mechanism involved in protective effects of prostacyclin against cardiac fibrosis was also studied. We found that beraprost, a prostacyclin analogue, inhibited angiotensin II (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 63 publications
(83 reference statements)
1
28
0
Order By: Relevance
“…Consequently, these Smad proteins represent intracellular therapeutic targets for the manipulation of TGF‐β1‐mediated fibrosis. The inhibition of TGF‐β1‐induced phosphorylation of Smad2 and Smad3 has been demonstrated in models of renal, hepatic, cardiac, and pulmonary fibrosis . Previous studies from our laboratory utilizing RNAi‐mediated knockdown models have shown that TGF‐β1‐mediated Smad2/3 phosphorylation is an essential step for fibroblast transdifferentiation to myofibroblasts .…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, these Smad proteins represent intracellular therapeutic targets for the manipulation of TGF‐β1‐mediated fibrosis. The inhibition of TGF‐β1‐induced phosphorylation of Smad2 and Smad3 has been demonstrated in models of renal, hepatic, cardiac, and pulmonary fibrosis . Previous studies from our laboratory utilizing RNAi‐mediated knockdown models have shown that TGF‐β1‐mediated Smad2/3 phosphorylation is an essential step for fibroblast transdifferentiation to myofibroblasts .…”
Section: Discussionmentioning
confidence: 96%
“…However, the vasculature is not the only site of IP expression in the myocardium. Although most of the IP mRNA in the mouse myocardium was found in noncardiomyocyte cells [6], this receptor was also reported to be expressed in such other cells as cardiac fibroblasts [2]. More detailed studies on isolated coronary arteries are needed to assess the actual expression levels of the IP in the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, activation of EP 4 and IP by synthetic analogs of prostaglandin E2 (PGE2) and prostacyclin, respectively, has been shown to inhibit TGFβ1-mediated synthesis of collagen type 1 and type 3 [65,66], and Ang-II-induced proliferation of rat cardiac fibroblasts [67]. These effects were shown to require cAMP production [65,67].…”
Section: Additional Gs-coupled Gpcr Regulating Fibrotic Responsesmentioning
confidence: 99%